Single-cell analysis of gene regulatory networks in the mammary glands of P4HA1-knockout mice. - Akshat Gupta; Lilin Huang; Jinpeng Liu; Ke Chen; Ren Xu; Wei Wu (PLoS Genetics)
Prolyl hydroxylation, catalyzed by collagen prolyl 4-hydroxylase (P4H), is a crucial post-translational modification involved in collagen biosynthesis. P4HA1, an isoform of P4H, plays a prominent role in stabilizing hypoxia-inducible factor-1α (HIF-1α). P4HA1 is frequently upregulated in highly aggressive triple-negative breast cancer, and has been implicated in tumor progression, metastasis, and chemoresistance. In this study, we investigated the role of P4HA1 in mouse mammary glands by analyzing gene regulatory networks (GRNs) in basal epithelial cells across two mouse groups: control (5Ht) and P4HA1-knockout (6Ho) mice. Specifically, we employed a single-cell network inference approach, integrating single-cell RNA sequencing with the SCENIC pipeline, and incorporated multiple validation strategies to construct gene regulatory networks (GRNs) specific to basal epithelial cells from each mouse group. Despite the inherent challenges of single-cell data, our approach identified reliable and reproducible GRN patterns across both the mouse groups. Based on these patterns, we identified subclusters of basal epithelial cells with similar regulatory profiles across the two mouse groups, as well as a unique subcluster in the control mice with a distinct regulatory pattern absent in the P4HA1-deficient 6Ho mice. This unique subcluster exhibited concurrent activation of stem cell development and inflammatory response pathways, suggesting the role of P4HA1 in regulating these biological processes linked to cancer initiation and progression. We verified these findings through multiple approaches, including in silico validation using multiple external datasets as well as experimental validation. Given that the loss of P4HA1 may disrupt stem cell development and inflammation response, our results suggest that targeting P4HA1 may offer a promising therapeutic strategy for breast cancer treatment.